THU0313 COMPARATIVE STUDY OF CLINICAL, ANALYTICAL AND VASCULAR 18F-FDG UPTAKE EVOLUTION IN PATIENTS WITH GIANT CELL ARTERITIS TREATED WITH METHOTREXATE VS TOCILIZUMAB. (June 2019) - Prieto-Peña, D.; Calderón-Goercke, Monica; Loricera, Javier; Narváez, J.; Aurrecoechea, Elena; Villa-Blanco, Ignacio; Castañeda, Santos; Gomez-Arango, Catalina; Varela, Antonio Mera; Perez-Pampín, Eva; Aldasoro, Vicente; Alvarez-Rivas, Noelia; et al.
Abstract : Background: Glucocorticoids remain to be the cornerstone therapy in giant cell arteritis (GCA). However, relapses are common when the prednisone dose is tapered. Thus, additional therapies are required in relapsing GCA. The most widely used conventional immunosuppressive drug is methotrexate (MTX) which efficacy is modest. Consequently, in some cases biological therapy in needed. Among them, the most frequently used is the recombinant humanized anti-IL6 receptor antibody tocilizumab (TCZ). 1 Objectives: To compare clinical evolution, normalization of acute phase reactants and normalization of vascular 18 F-FDG uptake assessed by PET/CT in patients with GCA treated with MTX vs TCZ. Methods: Comparative multicentric study of 23 patients with GCA treated with MTX vs 36 patients with GCA treated with TCZ who had a baseline and follow-up PET/CT scan. We assessed clinical improvement (no improvement/partial/complete), normalization of acute phase reactants (CRP ≤ 0.5mg/dL and/or ESR ≤ 20 mm/1 st hour) and reduction of 18 F-FDG uptake in PET/CT (no reduction/partial/complete normalization). Images were evaluated qualitatively by experienced nuclear medicine physicians. Prednisone tapering was also assessed. Statistical analysis was performed with SPSS. Student's t test or Mann-Whitney U test was used to compare continuous variables, and Chi-squared test or Fisher's exact test for categorical variables as appropriate. Results: We included 23 patients with GCA treated with MTX (20 women/3 men); mean age 65.6 ± 7.9 years; and 36 patients treated with TCZ (27 women/9 men); mean age 67.5 ± 8.3 years. Clinical, analytical and vascular 18 F-FDG uptake evolution is shown in the TABLE. After one year of treatment, the percentage of patients who experienced complete clinical improvement was higher in those who received TCZ (88.9% vs 44.4%; p=0.003). Normalization of acute phase reactants was also more frequent in patients who received TCZ (92.6% vs 47.6%; p=0.001). In regard with reduction of vascular 18 F-FDG uptake, complete normalization was only achieved in 25% of patients who received TCZ and 14.3% of those who received MTX. Conclusion: Patients with GCA who received TCZ experienced a more rapid and effective clinical and analytical improvement than patients who received MTX. Besides, prednisone tapering was quicker in patients with TCZ. However, no significant differences were found in complete normalization of 18 F-FDG vascular uptake between both treatments. Reference: [1] M. Calderón-Goercke et al. Tocilizumab in giant cell arteritis. Observational, open-label multicenter study of 134 patients in clinical practice. Semin Arthritis Rheum. (2019). doi: 10.1016/j.semarthrit.2019.01.003. [Epub ahead of print]) Disclosure of Interests: D. Prieto-Peña: None declared, Monica Calderón-Goercke: None declared, Javier Loricera: None declared, J. Narváez Consultant for: Bristol-Myers Squibb, Elena Aurrecoechea: None declared, Ignacio Villa-Blanco: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Catalina Gomez-Arango: None declared, ANTONIO MERA VARELA: None declared, Eva Perez-Pampín: None declared, Vicente Aldasoro: None declared, Noelia Alvarez-Rivas: None declared, Nagore Fernández-Llanio: None declared, María Álvarez del Buergo: None declared, Luisa Marena Rojas: None declared, Francisca Sivera: None declared, Eva Galindez: None declared, Roser Solans-Laqué: None declared, Susana Romero-Yuste: None declared, Isabel Martínez-Rodríguez: None declared, Jose Ignacio Banzo: None declared, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Ricardo Blanco Grant/research support from: Abbvie, MSD, and Roche, Consultant for: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen